Acceleration effect of a graphite dust environment on the fatigue crack propagation rates of Al alloy. (September 2019) - Chen, Y.Q.; Zhang, H.; Song, W.W.; Pan, S.P.; Liu, W.H.; Liu, X.; Zhu, B.W.; Song, Y.F.; Zhou, W.
Highlights: An experimental set-up for the fatigue testing in dusty environments was developed. The fatigue crack propagation rates were higher for the sample in graphite dust. The effect of graphite dust on fatigue crack growth diminished with increasing ΔK. The graphite dust environment decreased the crack closure levels during fatigue. Abstract: An experimental set-up for the fatigue testing of Al alloy in dusty environments was developed and the effect of a graphite dust environment on the fatigue crack propagation behaviour of 2524-T3 Al alloy was investigated. The fatigue crack propagation rates (FCGRs) are higher for the sample in graphite dust especially at low Δ K -levels and tends to be similar to those in air with increasing Δ K . This acceleration effect of graphite dust is due to the lubrication of the absorbed graphite particles on the mating fracture surfaces which decreases the extent of crack closure and promotes microcrack growth.